Numerical Simulation of Factors Influencing the Effectiveness of Orthokeratology Lens Correction - Junqi HU; Xiaojun WANG; Lihua ZHANG; Xiaona LI; Jie HOU (Taiyuan Ligong Daxue xuebao, 2024)
Purposes The corneal shape and mechanical properties of cornea and contact lens material have a certain impact on the correction effect of contact lens. Methods In this paper, a finite element model of corneal wearing orthokeratology lens was established by using hyperelasticity materials, and the biomechanical response of cornea after wearing lens was analyzed by changing the shape of cornea (different curvature and thickness) and the material parameters of cornea and orthokeratology lens. Findings The results showed that when the corneal curvature changed 4 m−1, the displacement difference at apex of the cornea central area changed by 15.7 μm, and when the corneal thickness changed by 75 μm, the displacement difference at apex of the central area changed by 12.3 μm; when the corneal material parameter k1 increased by 3 times, the change of displacement difference at apex of the cornea central area was 39.2 μm, when the C10 value increased by 4 times, the change of displacement difference was 55.5 μm, while when the orthokeratology lens material parameter E increased by 3 times, the change of displacement difference was only 0.2 μm. Conclusions When using orthokeratology lens to correct myopia, it is necessary to fully consider the influence of corneal morphology and the mechanical properties of the cornea on the correction effect.